Intention and Motivation in Online Arabic Courses: Agency for Learning Phenomenon - Abd. Rozak; Azkia Muharom Albantani; Mohamad Syafri (IAIN Salatiga, 2023)
This study examines the implementation of Arabic learning during the pandemic and explores students' intentions and motivations in learning Arabic online. The type used in this research is a qualitative approach. An exploratory investigative approach is used to investigate students' intentions and motivations in learning Arabic online. Data will be collected by distributing the questionnaire offline and online. The data was then used to analyse the intentions and motivations of second semester students of the Arabic Language and Literature Study Program at UIN Sultan Maulana Hasanuddin Banten to support the long-distance Arabic courses. The study results indicate that the overall average score is still above 4 on a scale of 6. It be interpreted that the students having good intentions and motivation in online Arabic lectures.